1998
DOI: 10.1046/j.1365-2044.1998.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal column function after epidural and spinal blockade: implications for the safety of walking following low‐dose regional analgesia for labour

Abstract: Walking after regional blockade for labour using low-dose combinations of bupivacaine and fentanyl is possible due to the maintenance of lower limb motor power. In order to investigate concerns that dorsal column function, important in maintaining balance, is impaired after such techniques, clinical assessment of lower limb proprioception and vibration sense was evaluated in parturients after either low-dose epidural (n = 30) or spinal blockade (n = 30) for labour analgesia and compared with spinal anaesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 21 publications
4
26
0
Order By: Relevance
“…5 We have also confirmed obstetric studies by showing that small doses of intrathecal agents spare both motor and proprioceptive fibres. 6 This effect is consistent with the dynamics of local anesthetic penetration and nerve fibre diameter-both motor and proprioceptive fibres are similar in diameter (12-20 µm). 7 On the other hand, pain sensation is mediated by the A* (2-5 µm) and the smaller C (0.3-1.3 µm) fibres that are more susceptible to local anesthetic block as found in this study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…5 We have also confirmed obstetric studies by showing that small doses of intrathecal agents spare both motor and proprioceptive fibres. 6 This effect is consistent with the dynamics of local anesthetic penetration and nerve fibre diameter-both motor and proprioceptive fibres are similar in diameter (12-20 µm). 7 On the other hand, pain sensation is mediated by the A* (2-5 µm) and the smaller C (0.3-1.3 µm) fibres that are more susceptible to local anesthetic block as found in this study.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, deficiency of one input can be compensated by increased input from the other systems as shown by clinical experience in patients with diseases that impair one system. 5,6 This suggests that ambulation after a small-dose spinal anesthetic which spares motor and dorsal column function, but selectively blocks the lateral spinothalamic tracts could be achieved with the help of compensatory inputs from other systems. Our study has confirmed that this is possible although no inferences can be made about safety of such practice.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that mean duration of analgesia was 126.46 seconds in group A and 125.68 seconds in group B, which was not significant, which is supported by the work of Lee B B et al 7 Maximum dermatome level achieved in both the groups are comparable and statistically not significant, which is again similar to the work of Lee BB et al and Parry MG et al 7,8 There was no difference between Bromage score that is 0 in both groups and also the haemodynamic parameters.…”
Section: Discussionsupporting
confidence: 81%
“…Motor block can occur after any top-up, but we found that it developed over about 10 min and did not result in sudden falls. The mother must be accompanied at all times if she leaves her room, as minor degrees of motor block and proprioception loss may make her more vulnerable to stumbling [13]. This was not a problem in the present study and we have always found that the mother herself is the best judge of her ability to mobilise safely.…”
Section: Discussionmentioning
confidence: 61%